A new species of the Liolaemus alticolor-bibronii group (Iguania: Liolaemidae) from East-central Argentina - Vega, Laura Estela; Quinteros, Andrés Sebastián; Stellatelli, Oscar Aníbal; Bellagamba, Patricio Juan; Block, Carolina; Madrid, Enrique Alberto (Zootaxa, 2018)
We describe a new species of Liolaemus of the L. alticolor-bibronii group of the subgenus Liolaemus sensu stricto. We studied meristic, morphometric and qualitative pattern characters. Statistical tests were performed in order to evaluate morphological differences among the candidate species and the most closely geographically distributed species. Molecular analyses of Cyt-b mitochondrial gene were performed in order to estimate the position of the new species in relation to other taxa. We also recorded natural history data such as habitat, behavior, reproductive state, diet, and body temperature. Liolaemus absconditus sp. nov. differs from other species of Liolaemus in presenting a distinct combination of morphological character states of lepidosis and color pattern, being phylogenetically close to Liolaemus tandiliensis, Liolaemus gracilis and Liolaemus saxatilis. The new species is a saxicolous and endemic lizard of the Tandilia Mountain Range System of Buenos Aires Province.